MiR-125b and miR-100 Are Predictive Biomarkers of Response to Induction Chemotherapy in Osteosarcoma. (21st November 2016) - Kubota, Daisuke; Kosaka, Nobuyoshi; Fujiwara, Tomohiro; Yoshida, Akihiko; Arai, Yasuhito; Qiao, Zhiwei; Takeshita, Fumitaka; Ochiya, Takahiro; Kawai, Akira; Kondo, Tadashi
Abstract : Osteosarcoma is the most common primary malignancy in bone. Patients who respond poorly to induction chemotherapy are at higher risk of adverse prognosis. The molecular basis for such poor prognosis remains unclear. We investigated miRNA expression in eight open biopsy samples to identify miRNAs predictive of response to induction chemotherapy and thus maybe used for risk stratification therapy. The samples were obtained from four patients with inferior necrosis (Huvos I/II) and four patients with superior necrosis (Huvos III/IV) following induction chemotherapy. We found six miRNAs, including miR-125b and miR-100, that were differentially expressed > 2-fold (p < 0.05 ) in patients who respond poorly to treatment. The association between poor prognosis and the abundance of miR-125b and miR-100 was confirmed by quantitative reverse transcriptase-polymerase chain reaction in 20 additional osteosarcoma patients. Accordingly, overexpression of miR-125b and miR-100 in three osteosarcoma cell lines enhanced cell proliferation, invasiveness, and resistance to chemotherapeutic drugs such as methotrexate, doxorubicin, and cisplatin. In addition, overexpression of miR-125b blocked the ability of these chemotherapy agents to induce apoptosis. As open biopsy is routinely performed to diagnose osteosarcoma, levels of miR-125b and miR-100 in these samples may be used as basis for risk stratification therapy.